Un bosque urbano en el desierto: conservación de la biodiversidad en Lima, Perú - Orellana Asenjo, Giancarlo Jeremy (2023)
The conservation of urban forests is a fundamental strategy to achieve sustainability and human well-being in the context of accelerated global urbanization. Lima, a megacity located in the desert, does not have the green infrastructure necessary to face its multiple problems. Therefore, the Project “Centro de la Diversidad Natural y Cultural del Perú” is being developed in the “Vivero Forestal” of the Universidad Nacional Agraria La Molina (UNALM) to be the main sample of the peruvian floristic and cultural richness. The aim of this study is to evidence the biodiversity conservation in the urban forest Vivero Forestal. We generated a census of trees, palms and some shrubs and herbaceous plants and a bibliographic review to identify the species of wild fauna. Furthermore, native species were identified according to their natural distribution and those that were threatened. The urban forest Vivero Forestal hosts in its 25 hectares 5 898 healthy individuals (78 forest species; 31 botanical families). 25% of the individuals are threatened (11 species). In addition, this urban forest has 32 native forest species of Peru (10 from the coast, seven from the highlands, and 15 from the rainforest). The Vivero Forestal is the habitat of species of fauna mainly of the coast: 66 birds (three threatened); one amphibian; four bats; one rodent and four reptiles (two threatened). Our study highlights this urban forest as the most biodiversity space in Lima; identifying the potential to become a Botanical Forest Park.